STUDY KELAYAKAN INVESTASI ALAT BERAT PADA INDUSTRI JASA KONTRUKSI JALAN - Edi Mawardi; Zakia Zakia; Bambang Tripoli (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
weight is very important in a construction work. The advantage of using heavy equipment is that it can get the job done faster. The use of heavy equipment that is not right will cause losses in terms of time, technical, and cost. For this purpose the feasibility of investing in heavy equipment is very necessary. A precise and complete analysis of operating costs for the heavy equipment will help the company to make decisions, especially in financial terms. The purpose of this study is to determine the feasibility of heavy equipment investment in the road construction industry. analysis of heavy equipment operating costs, and knowing good machine handling. Cost analysis on heavy equipment, is expected to provide benefits that can be feasible to invest in heavy equipment in the construction services industry. This research was carried out on the Project for Improvement of the Alun-Alun Suka Makmue Road-Phase II Eastern Ring Road, located in the Regency Nagan Raya. This study uses a qualitative method with a descriptive approach, namely research that tries to tell a solution to problems based on data that will be obtained in the field. This study uses a qualitative method with a descriptive approach, namely research that tries to tell a solution to problems based on data that will be obtained in the field. 738. per hour, motor grader Rp. 572,401 per hour, roller vibrator Rp. 499,735 per hour and water tanker truck Rp. 348,859 per hour. Whereas the economic age calculation is obtained for excavators, namely NVP = - Rp. 336. 421,545 <0 unfeasible, motor graders ie NVP = - Rp. 284. 7095,627 <0 unfeasible, vibrator roller NVP = Rp. 41,266,203> 0 feasible investment and water tanker truck that is NVP = Rp. 29,677,392> 0 feasible investment. The results show that excavator and motor grader heavy equipment has not yet returned capital, while for heavy equipment vibrator rollers and water tankers have returned capital. So for heavy equipment vibrator rollers and water tanker trucks are feasible to be replaced with a new device.Keywords: Heavy Equipment, Investment Feasibility and Operating Costs.